Navigating Complexity in Collaborative Environments through Innovations in Multi-Agent Multi-Armed Bandit Algorithms - Zhu, Siqi (Transactions on Computer Science and Intelligent Systems Research, 2024)
As Multi-Armed Bandit (MAB) applications grow increasingly complex, particularly when multiple agents collaborate or compete, traditional bandit algorithms face fresh challenges, underscoring the rising importance of research in multi-agent multi-armed bandits (MAMAB). Developments in MAMAB algorithms have spurred significant advances across a variety of fields, addressing challenges in dynamic and uncertain environments. This paper offers an exhaustive review of recent progress in MAMAB algorithms, emphasizing major strides in enhancing cooperative decision-making and operational efficiency. Our focus is particularly on the contributions of Filippo Vannella et al., who have explored sample complexity within the MAMAB framework. Their research signals a shift towards optimizing global actions by minimizing sample complexity and harnesses mean field techniques in contexts such as optimizing wireless networks. Additionally, this paper addresses communication complexity, a crucial aspect of MAMAB systems, where numerous novel algorithms have been developed. These algorithms strike a balance between performance and communication overhead, diminishing the need for frequent and costly interactions among agents. In application terms, the incorporation of MAMAB algorithms in sectors like clinical trials and wireless network spectrum management showcases their potential to revolutionize conventional approaches. Through a detailed examination of current research trends and prospective future directions, this article contributes to the broader discourse on harnessing MAMAB algorithms to navigate the complexities of collaborative environments effectively.